Assessing cognitive learning strategies: A global study of spanish learners - Di Carlo, Sergio (2017)
This article identifies and describes the types of cognitive language learning strategies used by learners of Spanish. Sample consisted of 665 participants, adult learners of Spanish from 60 universities and institutions. Data were collected with a self-completion multi-scale online survey. Descriptive statistical techniques (frequency distributions, arithmetic mean, standard deviation and percentage computing) were applied in analysis to achieve the objectives. Five theoretical categories were adopted to classify strategies according to their predominant function: classification, preparation, association, elaboration and transfer-practice. Thirty strategies were identified as the most used by the majority and all the five categories were present among these most used strategies. Data analysis confirmed different degrees of perceived usefulness on potential strategies. These findings suggest that different functional actions contribute to the comprehensive development of communicative competence.